Descriptive Study on the Self-Concept Levels of Instagram Users among Education Faculty Students at Kristen Indonesia University - Hasnaria Margaretha; Eustalia Wigunawati; Renatha Ernawati (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to find out, understand, and describe how the self-concept level of FKIP students uses Instagram. The method applied in this research is a type of quantitative research with a descriptive approach. The sampling technique in this study used a purposive sampling method. The total sample was 101 people and grouped by gender, age, Study Program at FKIP UKI, and duration of use of Instagram in three categories. This data collection method uses Google Meet because it can reach FKIP students at the Indonesian Christian University. In this study, in processing research and descriptive data analysis using SPSS version 25 while in self-concept categorization the analysis processing used JASP (Jeffrey’s Amazing Statistics Program) version 0.17.3. In this study, the subjects sampled were active students of the Indonesian Christian University FKIP who are also Instagram users. Based on the analysis carried out in this study, the results found that male students had a percentage of 15%, for students aged 18 years, there was a proportion of 25%, in the Guidance and Counseling Study Program, it was found that as many as 12.5% and on the duration of using Instagram for less than 30 minutes it is explained that there are 27.27% which are included in the high category.